“Something Works” in U.S. Jails: Misconduct and Recidivism Effects of the IGNITE Program - Marcella Alsan; Arkey Barnett; Peter Hull; Crystal S Yang (The Quarterly Journal of Economics, 2025)
Abstract A long-standing and influential view in U.S. correctional policy is that “nothing works” when it comes to rehabilitating incarcerated individuals. We revisit this hypothesis by studying an innovative law-enforcement-led program launched in the county jail of Flint, MI: Inmate Growth Naturally and Intentionally through Education (IGNITE). We develop an instrumental variables approach to estimate the effects of IGNITE exposure, leveraging quasi-random court delays that cause individuals to spend more time in jail before and after the program’s launch. Holding time in jail fixed, we find that one additional month of IGNITE exposure reduces weekly misconduct in jail by 25% and three-month recidivism by 24%, with the recidivism effects growing over time. Surveys of staff and community members, along with administrative test-score records and within-jail text messages, suggest that cultural change and improved literacy and numeracy scores are contributing mechanisms.